Low sintering temperature of lead magnesium niobate-lead titanate (0.9PMN-0.1PT) by adding oxide additives - Nuttapon Pisitpipathsin (2018)
© 2009 by World Scientific Publishing Co. Pte. Ltd. All rights reserved. This research work is aimed at lowering the sintering temperature of 0.9PMN 0.1PT ceramics by adding oxide additives. The oxides used for this purpose were Bi2O3 and Li2CO3 with various amounts, following the formula of xBi2O3+yLi2CO3, where x+y =10 mol% and x = 1, 3, 5 and the mixed oxide additive powders were then added to the dried powder of 0.9PMN 0.1PT with 1 wt% concentration. An excess PbO content of approximately 3 wtadded to all compositions to compensate the lead loss. After that, the mixed powders were pressed into pellets and subsequently sintered to form the ceramic samples. The results showed that the sintering temperature of 0.9PMN{0.1PT ceramics could be lowered down from 1250°C to 900{1000°C by the addition of small amount of the oxide additives, where the optimum composition was found in the sample with x: y = 1: 9 at sintering temperature of 1000°C. Moreover, the densication, dielectric and ferroelectric properties of this sample remain acceptable in particular uses, promising positive future for reduction of lead loss from electrical and electronic industries.